Estudos de ciclos de carga e descarga de reservatórios para armazenamento de gás natural adsorvido - Bastos Neto, Moisés (2005)
This study presents experimental data analyses of charge and discharge cycles in a prototype vessel of adsorbed natural gas (ANG) storage in a bed of activated carbon, compared with simulations obtained with a mathematical model proposed to foresee the behavior of pressure, average temperature and stored mass and delivery of natural gas in a given reservoir. To validate the model, each input parameter was independently calculated through analyses of the used carbon sample’s textural characteristics and the acquirement of adsorption equilibrium isotherms of methane in the same carbon sample. It was also obtained the adsorption isotherms of ethane, propane and butane, constituent of the natural gas (NG) in smaller proportions, for evaluation of the composition influence in the storage process efficiency. The textural characteristics analyses were run in a volumetric apparatus through the obtaining of nitrogen isotherms at 77 K. The adsorption equilibrium data of the NG components were acquired with the support of a magnetic suspension balance. In an initial stage, it was used experiments with natural gas and simulations with pure methane. The results showed discrepancies in the model prediction, leading to the conclusion that it is inadequate to assume that the natural gas presents behavior similar to the one of its larger proportion component, methane, for this case. Consequently, in another stage, simulations were compared with experiments using pure methane and a good agreement was observed in the results comparisons. Histories of pressure and stored mass were satisfactorily well predicted and, despite heat effects, not precisely taken into account in the model, there was a reasonably good agreement between simulation and experiment for the average temperature inside the vessel. Conclusively, the model was suitable for the prediction of the phenomena involved in an ANG storage process.